How do you evaluate (\frac { \sqrt { 25} } { 3} - \sqrt { 1} ) \cdot \frac { ( - 3) } { \sqrt { 16} } - (-2) \dot 3/(sqrt 64)?

1 Answer
Jan 6, 2018

-1/12

Explanation:

The way I usually approach problems like this is as follows:

Simplify square roots/stuff in square roots:

(\frac{\sqrt{25}}{3}-\sqrt{1}) \times \frac{-5}{\sqrt{16}}-(-2)\frac{3}{\sqrt{64}}
=(\frac{5}{3}-1)\times\frac{-5}{4}-(-2)\frac{3}{8}

Simplify stuff in parentheses:

=\frac{2}{3}\times\frac{-5}{4}-(-2)\frac{3}{8}

Multiply stuff and simplify fractions:

=\frac{-10}{12}-({-6}/8)
={-5}/6 - ({-3}/4)

Add and/or subtract, using common denominators for fractions if needed:

={-5}/6 + 3/4
={-10}/12 + 9/12
=-1/12